Quality of Life in Pelvic Organ Prolapse Patients with Operative Therapy at RSUP Dr. Mohammad Hoesin - Mutia Adilah Almenata; Hadrians Kesuma Putra; Septi Purnamasari; Ratih Krisna; Abarham Martadiansyah (Biomedical Journal of Indonesia, 2024)
Introduction. Pelvic organ prolapse is a condition where the pelvic organs descend from their original position and protrude into the vagina. This condition causes several complaints in the patients that can interfere with their daily activities and have an impact on their quality of life. One of the treatments that can be given to patients with POP is operative therapy, which one of the goals is to improve patient's quality of life. This study aims to determine the quality of life of pelvic organ prolapse patients with operative therapy at Dr. Mohammad Hoesin Hospital Palembang. Methods. This study used an observational analytical method with a cross-sectional study design. This study consisted of 17 respondents. This study used primary data from interviews using the P-QOL questionnaire guidelines and secondary data from medical records. Results. This study showed an improvement in the quality of life of pelvic organ prolapse patients in all P-QOL quality of life domains (p<0.05) after receiving operative therapy compared to before receiving operative therapy. Analysis of the effect of confounding factors on the total quality of life score showed that age (p=0.138), BMI (p=0.999), parity (p=0.468), degree of POP (p=0.439), and type of surgery (p=0.814) did not have a significant influence on the quality of life of postoperative POP patients. Conclusion. There was a significant improvement in the quality of life in pelvic organ prolapse patients after receiving operative therapy, and there is no significant relationship between age, BMI, parity, degree of POP, also type of surgery on the quality of life in postoperative POP patients.